Analysis of the Satisfaction Level of Bpjs Patients with Outpatient Registration Services - Zainal Siddiq; Ahmad Amiruddin; Mega Ermasari Muzuh (International Journal of Multidisciplinary Learners, 2025)
Puskesmas is an important and affordable form of health services and facilities for the entire community, and its location is easily accessible in each village or sub-district is the main reason people choose Puskesmas as a place to seek treatment.The outpatient registration place is the front service unit for each puskesmas. Patient registration services must be able to include important information about patient social data, one of which is the Bataraguru health center, especially in outpatient registration. The purpose of this study was to determine the level of satisfaction of BPJS patients with outpatient registration services based on five dimensions, namely, Reliability, Assurance, Empathy, Tangible, Responsiveness. This type of research uses quantitative descriptive research, this research design uses Cross Sectional and the type of sample used is Accidental Sampling. From the results of research conducted at the Bataraguru Health Center, Bau-bau City, it is known that of the 61 respondents, 57% stated that patients were very satisfied, 73% stated that patients were satisfied, and as many as 18% of patients were quite satisfied. In the Assurance variable, 50% stated that patients were very satisfied, 62% stated that patients were satisfied, and as many as 14% of patients were quite satisfied. In the Empathy variable, 62% stated that the patient was very satisfied, 62% stated that the patient was satisfied, and 14% of patients felt quite satisfied. In the Tangible variable, 52% stated that patients were very satisfied, 63% stated that patients were satisfied, 6% of patients were quite satisfied and 16% of patients were dissatisfied. In the Responsiveness variable, 91% stated that patients were very satisfied, 63% of patients were